Criminal protection of mass graves under the provisions of international humanitarian law - الغراوي, فاضل عبد الزهرة (Journal of Legal Sciences, 2021)
Genocide and crimes against humanity have a distinct meaning in that they are particularly reprehensible attacks that constitute a grave assault on human dignity or constitute a gross humiliation or degradation of the dignity of one or more human beings, and they are not isolated and sporadic incidents.That the crime of mass graves as a collective genocide is considered a mass murder of a group of people that is carried out on a discriminatory basis with the aim of their total annihilation as a race, people, or a distinct group that is culturally, culturally, linguistically or religiously independent, or for any reason that distinguishes them from humans, and this is what happened with the crime of mass graves in Iraq. We have noted that there is a close relationship between the crime of murder and genocide. In its commentary on the crime of genocide as one of the inhuman acts in its definition of crimes against humanity that violates the peace and security of humanity, we have noted this link and the most important thing that distinguishes them from each other is the direction of the nature of genocide against a group of individuals. Where the act committed for the commission of the crime includes the element of mass destruction found in the crime of mass graves that is not required by the crime of intentional murder.Regarding the application of international humanitarian law in Iraq, Iraq, despite its ratification of many international humanitarian law conventions, and whether the conflicts that took place in Iraq were in time of war or in time of peace, the previous regime overruled all international humanitarian law conventions by actions that He committed it against his people, including the act of killing or genocide represented by thousands of mass graves, which constitutes a legal act that must be punished and held accountable because when the Iraqi state recognized these rights and committed itself to treaties protecting them and signed the Universal Declaration of Human Rights, the Iraqi state and the issue of the regime must be held accountable for violations against These rights and non-compliance with their provisions, and the necessity of legal responsibility for these proven violations against the basic rights of the human being in Iraq, including his right to life, security, residence and freedom of movement and not forcing him to leave his home, stealing his property and forcibly transferring him to remote places in Iraq far from His usual place of residence and failure to give him the freedom for voluntary and safe return, as it is not sufficient for the state to agree to treaties Or the declaration or international covenants, but they must be respected and be subject to responsibility when violating them.The principle of national sovereignty or the issue of interference in the internal affairs of the state cannot be invoked to get rid of international obligations.